Mechanical properties of calcium carbonate and coconut shell filled polypropylene composites - Heidari, Mehdi (2012)
Natural lignocellulosics and mineral fillers have an outstanding potential as reinforcement in thermoplastics. This study deals with the preparation of coconut shell lignocellulosic and calcium carbonate mineral filler composites by reactive extrusion processing in which good interfacial adhesion is generated by a coupling agent of maleic anhydride. Polypropylene (PP) matrix was modified by reacting with maleic anhydride and subsequently bonded to the surface of the modified lignocellulosic component, in-situ. The PP was extruded with the fillers to form the compatibilized composite. These composite blends were then injection molded for mechanical characterization. Typical mechanical tests like tensile strength, flexural strength and Izod impact energy were performed and the results are reported. Also water absorption test was performed to assess the absorption value of moisture in the composite. Tensile properties of coconut shell and calcium carbonate filled polypropylene composites was increased and also the impact strength and elongation at break were increased too. Water absorption of PP filled coconut shell was increased significantly. These finding are discussed in view of the improved adhesion resulting from reactions and enhanced polar interactions at phase boundaries. The mechanical properties indicate that these fillers are desired as reinforcement for making a good composite.